ҚАРАҚАЛПАҚЛАРДЫҢ ӘМЕЛИЙ - БЕЗЕЎ ӨНЕРИ ГИЛЕМ ҲӘМ ГИЛЕМНЕН ИСЛЕНГЕН БУЙЫМЛАР - Уразимова, Т.В.; Бекжанов, К. (FAN va JAMIYAT, 2022)
The article is devoted to the issues of decorative-applied art of the Karakalpak people, and in particular carpets and rugs. The work reveals the specificity of manufacturing techniques, applications, compositional and coloristic features, and ornaments used in carpet weaving.